2011
DOI: 10.1002/art.30365
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis development in a novel rat model characterized by a single application of oxidative stress

Abstract: Objective. To investigate the relationship between transient oxidative stress and the development of osteonecrosis in a rat model.Methods. A total of 160 male Wistar rats (24 weeks old) were injected only once with the pro-oxidant DLbuthionine-(S,R)-sulfoximine (BSO) (500 mg/kg given intraperitoneally) and were killed 12 hours (group A), 1 day (group B), 3 days (group C), 4 days (group D), 5 days (group E), 7 days (group F), or 14 days (group G) after administration (n ‫؍‬ 20 per group). Twenty untreated rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…36,37 Recently, we reported that differences in liver function were observed between patients with corticosteroidinduced ONFH and those without ONFH within 1 week after corticosteroid therapy. 38 Moreover, Ichiseki et al 39 reported that a disturbance in oxidative stress in the liver was observed within 24 h in an oxidative stress-induced ONFH rat model. These reports suggest that various changes in the liver in the early phase after treatment contribute to the development of ONFH.…”
Section: Discussionsupporting
confidence: 49%
“…36,37 Recently, we reported that differences in liver function were observed between patients with corticosteroidinduced ONFH and those without ONFH within 1 week after corticosteroid therapy. 38 Moreover, Ichiseki et al 39 reported that a disturbance in oxidative stress in the liver was observed within 24 h in an oxidative stress-induced ONFH rat model. These reports suggest that various changes in the liver in the early phase after treatment contribute to the development of ONFH.…”
Section: Discussionsupporting
confidence: 49%
“…However, this model shows metaphysic osteonecrosis and not the epiphysic necrosis that is observed in human patients. To overcome these limitations, a rat model has been developed in which osteonecrosis is induced by excessive MP [12-14]. The rats genome is 90 percent similar to the human genome, and thus the pathological characteristics of osteonecrosis in rats and human may be similar.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ichiseki et al . reported oxidative stress‐induced ONFH in a rat model and demonstrated that glutathione level acts as an index of oxidative stress‐induced changes in the liver. Further, we previously reported that the disturbance of liver function was observed in patients with corticosteroid‐induced ONFH (Okazaki et al .…”
mentioning
confidence: 99%